2022
DOI: 10.1128/aem.00721-22
|View full text |Cite
|
Sign up to set email alerts
|

Merging Plastics, Microbes, and Enzymes: Highlights from an International Workshop

Abstract: In the Anthropocene, plastic pollution is a worldwide concern that must be tackled from different viewpoints, bringing together different areas of science. Microbial transformation of polymers is a broad-spectrum research topic that has become a keystone in the circular economy of fossil-based and biobased plastics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 104 publications
0
8
0
1
Order By: Relevance
“…While studies investigating the interaction between SRM and PHA degradation are scarce and largely limited to older culturebased studies, they demonstrated that PHAs can serve as carbon and electron source for sulfur reduction (Urmeneta et al, 1995) and that SRM are capable of causing pitting to the surface of PHA (Çetin, 2009). Desulfarulaceae may have uniquely evolved to utilize this substrate and they may be a promising source of bioplastic-degrading microbes and enzymes to complement efforts to recycle and valorize bioplastic waste (Jimeńez et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…While studies investigating the interaction between SRM and PHA degradation are scarce and largely limited to older culturebased studies, they demonstrated that PHAs can serve as carbon and electron source for sulfur reduction (Urmeneta et al, 1995) and that SRM are capable of causing pitting to the surface of PHA (Çetin, 2009). Desulfarulaceae may have uniquely evolved to utilize this substrate and they may be a promising source of bioplastic-degrading microbes and enzymes to complement efforts to recycle and valorize bioplastic waste (Jimeńez et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Aliphatic polyesters represent valuable plastic polymers that could be, in principle, depolymerized by microbial enzymes; however, apart from PET, limited studies are available on the specificity and efficiency of polyester-degrading enzymes and organisms in nature [ 217 ]. Recent studies investigated whether plastics spread in the environment stimulated the evolution of polyester degradation and assimilation of molecular machineries in microorganisms [ 220 , 221 ]. The collected evidence is not yet conclusive; the observed alteration of microbial diversity and genetic content could be an adaptation in response to the effects of the presence of toxic compounds rather than an adaptation to the use of plastics as a carbon source [ 222 ].…”
Section: Perspectivesmentioning
confidence: 99%
“…85 2.4. solutions, for example the use of natural products such as bamboo for pipes networks, 86 banana leaves 87 for packaging, seaweed as traps, 88 mussels as filters, 89 or microbes to breakdown microplastics. 90 Exploring and implementing natural options also have positive outcomes for biodiversity and addressing climate change issues. Life cycle assessments of alternatives need to be undertaken for all options to ensure that there is no shift of burden.…”
Section: Capacitymentioning
confidence: 99%
“…Environmental capacity includes knowledge and resources to use nature-based solutions, for example the use of natural products such as bamboo for pipes networks, banana leaves for packaging, seaweed as traps, mussels as filters, or microbes to breakdown microplastics . Exploring and implementing natural options also have positive outcomes for biodiversity and addressing climate change issues.…”
Section: Microplastics In the Context Of Disastermentioning
confidence: 99%